Wearable absorbent article with conductor arrangement
By using diethanol cellulose and conductive materials in absorbent articles, the problem of unpredictable absorption capacity saturation is solved by detecting humidity and liquids based on impedance, the detection accuracy and management efficiency are improved, and the cost is reduced and manufacturing complexity.
Patent Information
- Application Number
- CN202280096266.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-03
- Publication Date
- 2024-12-27
AI Technical Summary
Existing absorbent items such as diapers and medical dressings are difficult to accurately predict when the absorption capacity reaches saturation, resulting in leakage or inability to continue to absorb, increasing the management burden of caregivers, and the application of humidity sensors increases cost and manufacturing complexity.
Using a conductor arrangement structure composed of diethanol cellulose and conductive material, deposited on the material layer by printing technology, an impedance-based sensor is formed to detect humidity and liquid presence, simplifying the manufacturing process and reducing energy consumption.
It realizes cost-effective and environmentally friendly manufacturing of absorbent items, improves the detection accuracy and service life of absorbent items, reduces false negative measurement results, and allows remote detection of the presence of liquid.
Smart Images

Figure CN119212619A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a wearable absorbent article, such as a diaper, a sanitary napkin, an incontinence garment or a medical dressing, such as a wound dressing, comprising a conductor arrangement.
[0002] The present disclosure also relates to a method of making a wearable absorbent article with a conductor arrangement. Background Art
[0003] Wearable absorbent articles, such as diapers, sanitary napkins, incontinence garments, medical dressings and the like, have a wide range of uses in both domestic and institutional settings for purposes such as infant care, management of menstrual discharge, management of body exudates or secretions, and incontinence management. However, a known problem associated with the use of absorbent articles is that the articles have a limited absorbent capacity, which, if exceeded, causes the absorbent article to become ineffective, e.g., leak, or at least be unable to absorb further.
[0004] Therefore, the user of such articles or their caregivers must predict when the absorbent article is approaching its absorbent capacity and then must take steps to replace the article before capacity is reached. In situations where many users of such absorbent articles have relatively little care, such as in an institutional setting, managing the capacity of the various absorbent articles in use becomes a significant administrative burden.
[0005] It can be very difficult for a user or caregiver to accurately predict or determine the status of an absorbent article, both in terms of the absorbent capacity utilized and the need for replacement of the article. Even where the absorbent demand on the article is reasonably predictable, a period of record keeping and experimentation is required before a model can be developed and an appropriate absorbent article can be provided.
[0006] Therefore, a system that can alert a user or caregiver to saturation or impending saturation of an absorbent article is beneficial. Such a system may take the form of a moisture sensor for detecting moisture within an absorbent article. The moisture sensor may use a conductor arrangement disposed in a wearable absorbent article that is configured to detect moisture by measuring the resistance between different conductors of the conductor arrangement. In this manner, the moisture sensor is capable of determining both the amount of moisture and the location of a moisture event that has occurred in the absorbent article.
[0007] One approach to an absorbent article containing a wetness sensor is described in WO 2012 / 084987. It is also conceivable to include other sensors in a wearable absorbent article, such as infection sensors, hydration level sensors, etc.
[0008] The use of a wetness sensor does increase the cost of the absorbent article, and thereby the manufacturing process also becomes more complicated compared to an absorbent article without a wetness sensor.
[0009] Therefore, there is a need for an improved wearable absorbent article that addresses at least one of the above-mentioned disadvantages. Summary of the invention
[0010] Various aspects of the above-mentioned objects are achieved by a wearable absorbent article according to the present disclosure.
[0011] One aspect of the present disclosure relates to a wearable absorbent article comprising: at least one material layer; and a conductor arrangement at least partially deposited on the material layer. The conductor arrangement is formed from a composition comprising diethanol cellulose and a conductive material.
[0012] According to some embodiments, the conductor arrangement is at least partially printed onto the material layer.
[0013] According to some embodiments, the conductor arrangement structure is completely deposited on a plurality of material layers including the at least one material layer.The conductor arrangement structure may be completely deposited on the at least one material layer.
[0014] According to some embodiments, the conductor arrangement is completely printed on a plurality of material layers including the at least one material layer.The conductor arrangement may be completely printed on the at least one material layer.
[0015] The composition deposited on (e.g., printed on) at least one material layer or multiple material layers can be a conductive bio-ink comprising modified cellulose fibers, wherein the cellulose has been partially converted into diethanol cellulose, hereinafter referred to as diethanol modified cellulose (DALC) fibers. DALC fibers are highly flexible, ductile and can be melt processed. The conductive arrangement structure for manufacturing absorbent articles can allow the energy-consuming step of nanocellulose preparation to be omitted. In addition, the content of the desired conductive material can be reduced without compromising conductivity.
[0016] The absorbent article may be manufactured in a cost-effective and environmentally friendly manner because less energy may be consumed during the manufacturing process compared to when manufacturing other absorbent articles comprising a conductive arrangement.
[0017] According to some embodiments, the conductor arrangement comprises a sensing device or a part of a sensing device. The sensing device may comprise two elements and may be configured to measure the resistance between the two elements. According to some embodiments, the sensing device may be an impedance based sensor.
[0018] For some embodiments, the sensing device may be configured to detect one or several of infection, microbial growth, temperature, hydration level, etc. The sensing device may be a humidity sensor or another type of sensor.
[0019] According to some embodiments, the wearable absorbent article comprises a sensing device or a part of a sensing device in electrical contact with the conductor arrangement. The sensing device may comprise two elements and may be configured to measure the resistance between the two elements. According to some embodiments, the sensing device may be an impedance-based sensor.
[0020] The impedance value measured by the sensing device may change (e.g. decrease) in response to the introduction of liquid (e.g. urine) into a wearable absorbent article (e.g. a diaper or feminine hygiene article). Thus, the sensing device may be used to detect the presence of liquid (e.g. urine) in (a portion of) a wearable absorbent article. When the sensing device is configured to measure impedance, it may be deposited (printed) on at least one or several material layers such that no electrical contact between the sensing device and the liquid is required to detect the presence of the liquid. In other words, liquid absorbed by an absorbent layer of a wearable absorbent article may be remotely detected.
[0021] When using an additional sensing device located on the wearable absorbent article to make electrical contact with the conductive arrangement provided thereon, the concept of detecting liquid by means of a sensing element for measuring impedance allows obtaining a configuration in which the sensing device is located on the garment-facing surface of the wearable absorbent article. The latter positioning can in turn be associated with a reduced effort regarding the application and / or removal of the sensing device. Furthermore, attachment and / or detachment can be performed even when the wearable absorbent article is worn by a person, such as an infant or a patient.
[0022] According to some embodiments, the conductor arrangement comprises an additional sensing device or a part of an additional sensing device. The additional sensing device may comprise two elements and may be configured to measure the resistance between the two elements. According to some embodiments, the additional sensing device may be an impedance based sensor.
[0023] According to some embodiments, the wearable absorbent article comprises an additional sensing device or a part of an additional sensing device in electrical contact with the conductor arrangement. The additional sensing device may comprise two elements and may be configured to measure the resistance between the two elements. According to some embodiments, the additional sensing device may be an impedance-based sensor.
[0024] The presence of an additional sensing device may facilitate increased measurement accuracy. That is, if an additional second sensing device is provided in addition to the sensing device, a measurement of, for example, impedance may be achieved at at least two portions of the wearable absorbent article. Thus, it is possible to determine the presence of liquid in the wearable absorbent article even if liquid has not been introduced into the portion associated with the positioning of one of the sensing devices. Thus, it is less likely to receive a "false negative" measurement result.
[0025] Furthermore, the presence of more than one sensing device may allow conclusions to be drawn about the saturation of the wearable absorbent article.
[0026] According to some embodiments, the conductive arrangement is provided on the body-facing side of the wearable absorbent article.This may allow the presence of a fluid to be detected by direct (electrical) contact with the fluid.
[0027] According to some embodiments, the conductive arrangement is provided on the garment-facing side of the wearable absorbent article.This may allow for detecting the presence of a fluid indirectly, ie without (electrical) contact with the fluid.
[0028] A wearable absorbent article may include one or several fluid absorption areas for absorbing fluid, and an electronic device or a mounting location for mounting the electronic device, wherein a conductor arrangement structure electrically connects the electronic device or the mounting location for mounting the electronic device to at least one sensing location to detect the wetness of at least one or two or more areas in the fluid absorption area.
[0029] The electronic device may be the above-mentioned sensing device. The electronic device may be a device for transmitting a signal to an external device.
[0030] The conductor arrangement may include a plurality of elongated conductor lines extending along the extension direction. Each of the conductor lines may be electrically connected to a corresponding electrode, and each electrode may be arranged to contact a fluid absorption area of the wearable absorbent article.
[0031] The electronics may be configured to detect humidity at one or more locations within the fluid absorbing region by measuring the resistance of a conductor line between two of the electrodes.
[0032] At least some of the conductor lines may differ in cross-section and thus have different resistances.
[0033] The conductor wire may have a length in the corresponding extension direction in the range of 1 cm to 60 cm and / or 0.01 mm 2 Up to 1.00mm 2 The cross-sectional area within the range is perpendicular to the corresponding extension direction.
[0034] The fluid-absorbent region may comprise an absorbent core, and at least a portion of the conductor arrangement may be arranged so as to be electrically insulated from the absorbent core.
[0035] The electronic device may include a wetness detection unit that is removably attached to or embedded within the remainder of the wearable absorbent article.
[0036] The wearable absorbent article may be a diaper, a sanitary napkin or an incontinence garment.
[0037] The wearable absorbent article may be a medical dressing, such as a wound dressing. The medical dressing may include a wound contact layer, an absorbent core, and a backing layer.
[0038] According to some embodiments, the conductor arrangement includes a ground electrode and a capacitor electrode, and the ground electrode may form a closed loop around the capacitor electrode.
[0039] The material layer may include at least one item selected from the group consisting of: flexible materials such as nonwovens, films, tissues and fabrics.
[0040] The conductor arrangement may comprise between 5 and 70 weight % of the electroactive material.The conductor arrangement may comprise between 30 and 95 weight % of diethanol cellulose.The conductor arrangement may comprise between 10 and 80 weight % of the plasticizer.
[0041] As used in this article, the term "plasticizer" generally refers to the material or material that is combined in the matrix forming material to increase its flexibility or processability. Many plasticizers tend to reduce the intermolecular force between the polymer chains, causing the flexibility and compressibility of increase, or they can play plasticizing, because they cause discontinuity in the polymer matrix. The example of plasticizer class is sugar (monose, disaccharide or oligosaccharide), ethanol, polyol, acid, salt, fat and derivative (for example fatty acid, monoglyceride, ester, phospholipid) and surfactant class. The specific example of suitable plasticizer includes but is not limited to: glucose, fructose, sorbitol, polyethylene glycol, glycerine, propylene glycol, lactitol, sodium lactate, hydration hydrolyzed starch, trehalose or its combination, for example honey. Other applicable plasticizers used in the present disclosure include DMSO and ionic liquid.
[0042] The conductive material may include a conductive polymer. The conductive polymer may be PEDOT:PSS. "PEDOT:PSS" is a polymeric compound, also known as a polymer complex, including poly-3,4-ethylenedioxythiophene (PEDOT) and polystyrene sulfonate (PSS) in any ratio. PEDOT:PSS is available from multiple suppliers and is often used in conductive bio-inks because it is easy to use. A PEDOT:PSS ratio of 1:2.5 can be used to form the conductive material, however, it is generally understood that changing the ratio is also possible.
[0043] Conductive polymers such as PEDOT:PSS can provide advantages as components for conductive arrangements because they are electroactive components that provide benefits in terms of their processability, electrochemical properties, and charge transfer capabilities. Such polymers may have required doping with solvents such as ionic liquids, concentrated sulfuric acid, or dimethyl sulfoxide (DMSO) to increase their electronic conductivity for use in electronic devices. However, in the composition for the conductive arrangement according to the present disclosure, no organic solvent may be required to be added. This can provide benefits in terms of manufacturability, cost efficiency, and environmental friendliness.
[0044] According to some embodiments, the conductor arrangement has a conductivity of at least 0.05 S / cm. It may have a conductivity of at least 0.1 S / cm. It may have a conductivity of at least 0.5 S / cm. It may have a conductivity of at least 1 S / cm.
[0045] Diethanol cellulose may include fibers having a diameter of at least 1 μm (and, according to some embodiments, no fibers having a smaller diameter). According to some embodiments, diethanol cellulose includes fibers having a diameter of at least 5 μm (and, according to some embodiments, no fibers having a smaller diameter). Diethanol cellulose may include fibers having a diameter of at least, for example, at least 8 μm (and, according to some embodiments, no fibers having a smaller diameter). Diethanol cellulose may include fibers having a diameter of at least 12 μm (and, according to some embodiments, no fibers having a smaller diameter).
[0046] The diethanol cellulose may comprise nanofibrils having a diameter of less than 1000 nm, alternatively less than 500 nm, or less than 200 nm, or less than 100 nm, or 50 nm.
[0047] Plasticizers may include polyols.
[0048] The polyol may be selected from the group consisting of glycerol, sorbitol and erythritol.
[0049] The polyol may include glycerol.
[0050] The plasticizer may include DMSO.
[0051] Plasticizers may include ionic liquids.
[0052] When the conductive arrangement structure includes a conductive polymer, the conductive polymer may include one or more polymers selected from the group consisting of: polyphenylene, polypyrene, polyazulene, polynaphthalene, polyacetylene (PAC), poly-p-phenylenevinylene (PPV), polypyrrole (PPY), polycyclopentane, polyaniline (PANI), polythiophene (PT), poly-3,4-ethylenedioxythiophene (PEDOT), toluenesulfonyl (Tos) and polystyrenesulfonate (PSS).
[0053] The conductive arrangement may comprise between 10% and 50% by weight of the conductive polymer.
[0054] The electrically conductive arrangement may comprise at least 40 wt % of an electrically conductive polymer.
[0055] The electrically conductive arrangement may comprise electrically conductive carbon.
[0056] The conductive carbon may be selected from the group consisting of 1D carbon, 2D carbon and 3D carbon. The 3D carbon may be graphite. The 2D carbon may be graphene. The 1D carbon may be carbon nanotubes.
[0057] The conductive arrangement may include a conductive 2D material. The conductive 2D material may be selected from the group consisting of graphene, MXene and molybdenum disulfide (MoS2).
[0058] Another aspect of the present disclosure relates to a method for manufacturing a wearable absorbent article. The method includes the steps of providing an absorbent article including at least one material layer, and depositing a composition including diethanol cellulose and a conductive material on the at least one material layer to form a conductor arrangement structure on the at least one material layer.
[0059] According to some embodiments, the composition is deposited on the at least one material layer by any one or several of the following techniques: 3D printing, 2D printing, screen printing, stencil printing, doctor blading, melt processing, slot die coating, inkjet printing, laser printing, solution processing, vacuum filtration, solvent casting, and papermaking technology.
[0060] Before, during and / or after applying the composition, the composition may be at least partially dried.
[0061] Before, during and / or after applying the composition, the composition may be at least partially cured.
[0062] The method may further comprise one or more additional steps of adding a cross-linking agent before, during and / or after applying the composition.
[0063] As used herein, the term "cross-linking agent" or "cross-linker" refers to a chemical entity capable of forming cross-linked chains between polymers; and an agent capable of providing cross-linking of polymer chains in the presence of an appropriate reactant (e.g., gamma radiation or other types of electromagnetic radiation or electron bombardment).
[0064] The crosslinking agent may be added before, during and / or after application of the composition.
[0065] Another aspect of the present disclosure relates to an absorbent article made according to any aspect of the method of the present disclosure.
[0066] Additional advantages and features of the present disclosure (which can be achieved by themselves or in combination with one or several of the features discussed above, as long as the features are not mutually inconsistent) will become apparent from the following description of specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] For a better understanding of the present disclosure and to show how it may be implemented, reference will now be made, by way of example only, to the accompanying drawings in which:
[0068] The description is given with reference to the accompanying drawings, in which:
[0069] Figure 1a depicts a top view of a wearable absorbent article according to one embodiment of the present disclosure;
[0070] Figure 1b depicts a cross-sectional view along line AA in FIG. 1 ;
[0071] Figure 2 a depicts a conductive arrangement printed onto a material layer of one embodiment of a wearable absorbent article according to the present disclosure;
[0072] Figure 2 b is Figure 1a an enlarged view of a portion A of;
[0073] Figure 3a depicts a conductive arrangement printed onto a material layer of one embodiment of a wearable absorbent article according to the present disclosure;
[0074] Figure 3b depicts a conductive arrangement printed onto a material layer of one embodiment of a wearable absorbent article according to the present disclosure;
[0075] Figure 4ashows a portion of a schematic process for preparing diethanol modified cellulose fibers for use in a conductive arrangement on a wearable absorbent article;
[0076] Figure 4b shows a portion of a schematic process for preparing diethanol modified cellulose fibers for use in a conductive arrangement on a wearable absorbent article;
[0077] FIG5 shows the results of rheological analysis of 3D conductive inks at different solid contents obtained from the compositions used in the conductive arrangement deposited on the wearable absorbent article;
[0078] Figure 6 AFM image showing PEDOT:PSS particles modified on diethylcellulose nanofibrils in fibers;
[0079] Figure 7 Surface of a 3D printed film obtained from a composition used in a conductive arrangement deposited on a wearable absorbent article ( Figure 7 a) and cross section ( Figure 4b )image;
[0080] Figure 8 shows the 3D printed membrane before washing ( Figure 8a ) and after ( Figure 8b ) of the embodiment;
[0081] Fig. 9 comparing the wetting characteristics of a 3D printed film using a non-DALC composition to a 3D printed film using a composition used in a conductive arrangement deposited on a wearable absorbent article before and after washing;
[0082] Fig.10 showing different 3D printed structures of a composition used in a conductive arrangement deposited on a wearable absorbent article;
[0083] Fig.11 shows the conductivity of a 3D gel printed using an embodiment of a composition used in a conductive arrangement deposited on a wearable absorbent article;
[0084] Fig.12 shows conductivity measurements of other 3D printed films soaked in water or phosphate buffered saline (PBS) using compositions used in conductive arrangements deposited on wearable absorbent articles;
[0085] Fig.13 a shows the relative resistance as a function of stretching a 3D serpentine pattern printed using a composition used in a conductive arrangement deposited on a wearable absorbent article;
[0086] Fig.13 b shows Fig.13 a Simple conductive function of the serpentine pattern;
[0087] Fig.14 Schematic test configuration for electrochemical testing of 3D samples, including reference electrode RE (Ag / AgCl); counter electrode CE (Pt electrode); and working electrode WE (3D printed sample mounted on Pt wire), the 3D sample printed using a composition used in a conductive arrangement structure deposited on a wearable absorbent article;
[0088] Fig.15 Shown from Fig.14 Measurement results obtained with the test configuration;
[0089] Fig.16 Shown from Fig.14 Measurement results obtained with the test configuration;
[0090] Fig.17 Shown from Fig.14 Measurement results obtained with the test configuration;
[0091] Fig.18 Shown from Fig.14 Measurement results obtained with the test configuration;
[0092] Fig.19 Shown from Fig.14 Measurement results obtained with the test configuration;
[0093] Fig. 20 Examples of fabricated supercapacitor devices are shown that include examples of the extruded compositions. Fig.15 Shown from Fig.14 Measurement results obtained with the test configuration;
[0094] Fig.21 Show Fig. 20 Constant current charge / discharge curves of the device;
[0095] Fig. 22 ECG measurements from a wearable electrode device are shown. DETAILED DESCRIPTION
[0096] Figure 1a Depicted is a top view of a wearable absorbent article according to the present disclosure. This embodiment is a diaper 1 .
[0097] The diaper 1 comprises a main portion 15, a first side portion 16, a second side portion 17 and an attachment member 7. The main portion 15 is elongated in a first direction. The first direction is parallel to the longitudinal centerline of the wearable absorbent article. The longitudinal centerline extends from a front side 2 of the absorbent article, which faces the front side of the wearer in use of the absorbent article, to a back side 3 of the absorbent article, which faces the back side of the wearer in use of the absorbent article.
[0098] The first and second side portions 16,17 extend away from the main portion 15 in a second direction perpendicular to the first direction. The first and second side portions 16,17 extend away from the main portion 15 on opposite sides of the main portion 15. The attachment member 7 is provided on both side portions 16,17.
[0099] Figure 1b Describe along Figure 1a Cross-sectional view of line AA.
[0100] The diaper 1 has a liquid-permeable top layer 8, a liquid-impermeable bottom layer 9, and an absorbent core 13. The top layer 8 is adapted to face the wearer during use and allow fluid (such as urine or other body fluids) to pass through, the bottom layer 9 is opposite to the top layer 8 and is adapted to prevent fluid from passing through, and the absorbent core 13 is positioned between the bottom layer 9 and the top layer 8 for absorbing fluid.
[0101] The diaper 1 is configured to be worn around the waist of a user by attaching the side portions 16 , 17 to the main portion 15 using the attachment member 7 .
[0102] Furthermore, the diaper 1 is provided with an electrically conductive arrangement 20 which is printed onto the backing layer 9 .
[0103] Although it has been combined Figure 1a and Figure 1b Diapers are described, but the present disclosure also covers other embodiments of wearable absorbent articles provided with a conductor arrangement according to the present disclosure. Figure 1a and Figure 1b A similar or identical conductor arrangement in the embodiment of the present invention may for example be printed onto a medical dressing such as a wound dressing, or onto a sanitary napkin or incontinence garment.
[0104] Figure 2 a depicts a conductive arrangement 20 printed onto a material layer of a first embodiment of a wearable absorbent article according to the present disclosure.
[0105] The conductive arrangement may for example be printed on a diaper, a sanitary napkin, an incontinence garment or a medical dressing. The example of a diaper will be discussed in further detail.
[0106] For example, the conductive arrangement 20 may be printed onto one of the layers of the diaper 1 of Figure 1. A different embodiment is, for example, a wound dressing with the conductive arrangement 20 printed onto one of the layers. Figure 2 A conductive arrangement structure.
[0107] The conductor arrangement 20 is formed from a composition comprising diethanol cellulose and a conductive material and it forms part of a sensing device for detecting wetness in a diaper.
[0108] The conductor arrangement 20 includes a plurality of elongated conductor wires and electrode wires, each of which is electrically connected to a corresponding one of the conductor wires. The conductor arrangement 20 has a humidity detection unit (not shown) attached thereto, a control unit (not shown) for controlling the humidity detection unit, and a power source (not shown) for providing power to the control unit and the humidity detection unit.
[0109] The conductor arrangement may further include a transmitter for transmitting information related to the humidity detected by the humidity detection unit or other related information. The conductor arrangement may further include a receiver for receiving information (eg, instructions).
[0110] The conductor arrangement structure includes between 5 wt % and 70 wt % of the electroactive material, between 30 wt % and 95 wt % of diethanol cellulose, and optionally between 10 wt % and 80 wt % of a plasticizer. The conductive material includes a conductive polymer. The conductive polymer includes poly-3,4-ethylenedioxythiophene and polystyrene sulfonate.
[0111] The conductive arrangement is printed onto a material layer of the diaper 1 in the main part 15 of the diaper 1. It may for example be printed onto the layer facing the absorbent core 13, on the body facing side or on the garment facing side, depending on the type of sensing technology used.
[0112] The power source may hold an energy storage in the form of electrical energy and / or chemical energy. The power source may be any type of power source, such as a battery cell, a battery and / or a capacitor. For example, the power source may be a flexible paper battery cell / battery, such as those provided by BlueSpark Technologies (OH, US), Enfucell Oy (FI), GS Nanotech (KR) or Cymbet (MN, US).
[0113] The conductor arrangement 20 has a conductivity of at least 0.05 S / cm, optionally at least 0.1 S / cm or at least 0.5 S / cm, or at least 1 S / cm.Diethanol cellulose comprises fibers having a diameter of at least 1 μm, such as at least 5 μm, such as at least 8 μm, such as at least 12 μm.
[0114] The conductor arrangement 20 comprises a plurality of elongated conductor lines 4, each of which extends in the same extension direction. The extension direction of the conductors 4 is parallel to the longitudinal centerline of the wearable absorbent article (see, for example, the diaper 1 of FIG. 1 ). Each conductor line 4 has been printed onto a material layer of the wearable absorbent article.
[0115] exist Figure 2 In the case of the embodiment of a, the conductor wires 4 have different lengths in the extending direction. The conductor wires 4 that are longer in the extending direction can have a lower resistance per unit length than the conductor wires that are shorter in the extending direction.
[0116] In particular, as in Figure 2 As schematically shown in the enlarged view of FIG. 1 b, the longer conductor wire 4 has a larger cross-sectional area perpendicular to the extension direction than the shorter conductor wire 4. In this way, the resistance difference (i.e., the overall resistance or total resistance) of the conductor wire 4 associated with the length difference can be reduced or even eliminated in a particularly simple and effective manner. However, for other embodiments, the conductor wires 4 with different lengths can have the same cross-section.
[0117] In addition, those conductor wires 4 having a longer length in the extension direction can be made of a material (e.g., metal and / or metal alloy) that has a lower resistance than the material (e.g., metal and / or metal alloy) among the conductor wires 4 having a shorter length in the extension direction.
[0118] The cross-sectional area and / or the material of the conductors 4 may be selected such that all conductors 4 have substantially the same resistance.
[0119] Each of the conductor lines 4 of the conductor arrangement 20 is electrically connected to an electrode line 6, such as Figure 2 Specifically, each of the electrode wires 6 is electrically connected to the corresponding conductor wire 4 at the distal end of the conductor wire 4 in the extending direction thereof (ie, the end of the conductor wire 4 disposed farther from the humidity detection unit (not shown)).
[0120] All electrode wires 6 extend along the same extension direction. The extension direction of the electrode wires 6 is substantially perpendicular to the extension direction of the conductor wires 4. All electrode wires 6 have substantially the same length in the extension direction.
[0121] The conductor wire 4 and the electrode 6 are arranged between the insulating substrate 24 and the insulating layer 25, so that the conductor wire 4 is covered by the insulating layer 25 and the electrode wire 6 is exposed through the opening 26. In this way, it can be reliably ensured that the conductor wire 4 is electrically insulated from the absorbent core of the wearable absorbent article, and the electrode 6 can be arranged to contact the absorbent core in a simple and effective manner. In this way, when a wetting event occurs in the absorbent core, electrical contact is established between the corresponding one or more of the electrode wires 6 and the absorbent core.
[0122] The humidity detector (not shown) is configured to detect humidity at one or more locations within the absorbent core by measuring the resistance between adjacent ones of the electrode lines 6 (i.e., the electrode lines 6 adjacent to each other) through the conductor line 4. In particular, the resistance is measured at the electrical contacts 27, each of which is electrically connected to the corresponding conductor line 4 at the proximal end of the conductor line 4 in the direction of its extension (i.e., at the end of the conductor line 4 arranged closer to the humidity detection unit) (see Figure 2 a and Figure 2 b) These electrical contacts 27 are arranged adjacent to each other along the extension direction of the conductor line 4, ie along the longitudinal center line of the wearable absorbent article.
[0123] for Figure 2 In an embodiment of the present invention, the conductive arrangement 20 can be printed onto the material layer of the diaper at a position that makes the electrode wires 6 contact the absorbent core of the diaper, while the conductor wires 4 are electrically insulated from the absorbent core by the insulating layer 25. When a wetting event occurs in the absorbent core, electrical contact is established between the corresponding ones of the electrode wires 6 and the absorbent core. In this way, electrical contact is established between at least two of the electrode wires 6 through the absorbent core.
[0124] The humidity detection unit (not shown) is configured to detect humidity at one or more locations within the absorbent core by measuring the resistance between at least two (e.g. adjacent) of the electrode wires 6 through the conductor wire 4. The resistance is measured at the electrical contacts 27 (see Figure 2 a and Figure 2 b), as described in detail above.
[0125] Figure 3a Depicts a conductive arrangement printed onto a material layer of one embodiment of a wearable absorbent article according to the present disclosure. The conductive arrangement may be printed, for example, on a diaper, sanitary napkin, incontinence garment, or medical dressing.
[0126] Figure 3b Depicts a conductive arrangement printed onto a material layer of one embodiment of a wearable absorbent article according to the present disclosure. The conductive arrangement may be printed, for example, on a diaper, sanitary napkin, incontinence garment, or medical dressing.
[0127] Figure 3a and Figure 3b The conductive arrangement structure depicted in the figure is configured to include a sensing element 10, and a corresponding shielding component 18 is continuously arranged between a corresponding grounding element (including a corresponding grounding electrode line 12 and a corresponding grounding line 20) and a corresponding signal line 14, so that there is no part of the sensing element 10 between the grounding element and the signal line 14 in which the corresponding shielding component 18 is not arranged.
[0128] As explained above, the conductive arrangement at least partially deposited onto one or several material layers of the wearable absorbent article according to the present disclosure is formed from a composition comprising diethanol cellulose and a conductive material.
[0129] "Diethanol cellulose" or "DALC" or "diethanol modified cellulose fibers" refers to cellulose fibers that can be modified, for example, by Figure 4a and Figure 5b Modified cellulose obtainable by the method shown in . The method includes oxidizing cellulose in a fiber suspension to dialdehyde cellulose, followed by reducing the dialdehyde cellulose to obtain diethanol cellulose. Some methods for obtaining DALC are further discussed in patent application WO2018 / 135994. These terms also incorporate DALC nanofibrils, cellulose-based nanofibrils obtainable by microfluidization or mechanical processing of DALC fibers. It should be understood that although cellulose nanofibrils and diethanol-modified fibers can be referred to as diethanol cellulose, the nanofibrils have a smaller nanometer diameter, such as less than 1000nm, preferably less than 500nm, or less than 200nm, or less than 100nm, or 50nm, while the fibers are in the micrometer range, and may have, but are not limited to, a diameter of at least 1μm, such as at least 5μm, such as at least 8μm, such as at least 12μm. The length of the fibers and nanofibrils can be in the micrometer or millimeter range.
[0130] In general, when referring to DALC cellulose, it is understood that a certain amount of cellulose has been modified. Typically, the desired modification depends on the application. However, in general for the applications disclosed herein, a degree of modification or substitution of 10%-50% is sufficient. However, lower or even higher degrees of substitution or modification may also be used.
[0131] "PEDOT:PSS" is a polymeric compound, also known as a polymer complex, comprising poly-3,4-ethylenedioxythiophene (PEDOT) and polystyrene sulfonate (PSS) in any ratio. PEDOT:PSS is available from multiple suppliers and can be used in conductive bio-inks because of its ease of use. If not otherwise mentioned, a PEDOT:PSS ratio of 1:2.5 is used, however, it is generally understood that varying the ratio is possible and is considered within the scope of the present disclosure.
[0132] DALC-based bioink
[0133] The composition for forming a conductive arrangement structure deposited on a wearable absorbent article according to the present disclosure may include diethanol cellulose and an electroactive material. The diethanol cellulose in the present disclosure may be in the form of DALC fibers or DALC nanofibrils. DALC fibers and nanofibrils can be prepared using methods known to those skilled in the art. For example, DALC fibers can be obtained by oxidizing cellulose in a fiber suspension to dialdehyde cellulose, followed by reducing the dialdehyde cellulose to obtain diethanol cellulose. As desired, DALC nanofibrils can then be obtained by microfluidization or mechanical processing of DALC fibers.
[0134] The composition may further include a plasticizer.
[0135] The electroactive material in the bio-ink refers to any material that transmits an electric current, e.g., a conductive material. In some embodiments, the composition includes between 5% and 70% by weight of the electroactive material. In some embodiments, the composition includes between 10% and 50% by weight of the electroactive material. In some embodiments, the composition includes 40% by weight of the electroactive material.
[0136] In some embodiments, the composition includes between 30% and 95% by weight diethanolcellulose.
[0137] In some embodiments, the composition includes between 10% and 80% by weight plasticizer, such as between 15% and 75% by weight plasticizer. Alternatively, the composition may include between 1% and 10% by volume plasticizer.
[0138] The conductivity of the conductive arrangement may be about 0.1 S / cm. In some embodiments, the composition has a conductivity of at least 0.05 S / cm, such as at least 0.1 S / cm, such as at least 0.5 S / cm, such as at least 1 S / cm.
[0139] In some embodiments, the plasticizer includes a polyol. Examples of polyol plasticizers include glycerol, sorbitol, and erythritol. In some embodiments, the plasticizer includes glycerol. As shown in these examples, glycerol in combination with DALC and PEDOT:PSS enhances the separation of PEDOT and PSS, thereby increasing the conductivity of the composition. The addition of glycerol also enables the composition to maintain the gel properties of the ink, increased wet stability, and adhesion of the ink to the substrate. Compared to conventional hydrogel materials, the wet stability and ability of the composition to retain moisture based on the composition of the present disclosure can extend the shelf life of the device.
[0140] In some embodiments, the plasticizer comprises DMSO.
[0141] In some embodiments, the plasticizer comprises an ionic liquid.The term "ionic liquid" is generally defined as a molten salt that is composed of ions and is liquid at certain temperatures.
[0142] In some embodiments of the present disclosure, the electroactive material includes a conductive polymer. It should be understood that the term "conductive polymer" may also include a mixture or composite comprising several polymers, which may or may not have conductive properties themselves, provided that the mixture exhibits conductive properties. The conductive polymer may, for example, include one or more polymers selected from the group consisting of polyphenylene, polypyrene, polyazulene, polynaphthalene, polyacetylene (PAC), poly-p-phenylene vinylene (PPV), polypyrrole (PPY), polycyclopentane, polyaniline (PANI), polythiophene (PT), poly-3,4-ethylenedioxythiophene (PEDOT), toluenesulfonyl (Tos) and polystyrenesulfonate (PSS).
[0143] In some embodiments, the conductive polymer includes PEDOT:PSS.
[0144] In some embodiments, the composition includes between 5 wt % and 70 wt % of the conductive polymer.
[0145] In some embodiments, the composition includes between 10% and 50% by weight of the conductive polymer.
[0146] In some embodiments, the composition includes 40 wt % of the conductive polymer.
[0147] In some embodiments, the electroactive material comprises a conductive carbon material. The term "conductive carbon material" may include any carbon allotrope that conducts electricity. Based on the size structure of the electron restriction, the carbon can be classified as OD, 1D, 2D and 3D carbon. In some embodiments, the conductive carbon material is selected from the group consisting of: 1D carbon, 2D carbon and 3D carbon.
[0148] In some embodiments, the 3D carbon is graphite.
[0149] In some embodiments, the 2D carbon is graphene.
[0150] In some embodiments, the 1D carbon is a carbon nanotube.
[0151] In some embodiments, the electroactive material comprises a conductive 2D material. The 2D material may be an organic or inorganic conductive material characterized by a 2D structure. In some embodiments, the conductive 2D material is selected from the group consisting of graphene, MXene, and molybdenum disulfide (MoS2).
[0152] Hereinafter, a method for making a composition for forming a conductive arrangement deposited on a wearable absorbent article according to the present disclosure will be described. The method comprises the step of mixing diethanol cellulose with an electroactive material, thereby obtaining the composition.
[0153] In some embodiments, the method of making the composition further comprises a subsequent step wherein a plasticizer is mixed with the diethanol cellulose and the electroactive material.
[0154] Processing of bio-inks
[0155] The bio-ink can be further processed into a conductive material. Examples of processing techniques include, but are not limited to, extrusion, printing, or solution processing techniques.
[0156] In some embodiments, the conductive material is obtained by applying the composition to a wearable absorbent article by 3D printing, 2D printing, screen printing, stencil printing, doctor blading, melt processing, molding, slot die coating, inkjet printing, laser printing, solution processing, vacuum filtration, solvent casting, and / or papermaking techniques.
[0157] In some embodiments, the composition is at least partially dried before, during, and / or after applying the composition.
[0158] In some embodiments, the composition is at least partially cured before, during, and / or after applying the composition.
[0159] A crosslinking agent may be added to the composition to give it a 3D network structure. In some embodiments, the composition further comprises a crosslinking agent. The crosslinking agent may be added before, during and / or after applying the composition. In some embodiments, the crosslinking agent is selected from the group consisting of: an ionic crosslinking agent, a photocrosslinking agent, and a covalent crosslinking agent.
[0160] In some embodiments, the conductive material has a conductivity between 0.05 S / cm and 150 S / cm, such as between 0.1 S / cm and 100 S / cm, such as 40 S / cm, such as 35 S / cm, such as 30 S / cm. In some embodiments, the conductive material has a conductivity of at least 0.05 S / cm, such as at least 0.1 S / cm, such as at least 0.5 S / cm, such as at least 1 S / cm, preferably it has a conductivity of at least 0.1 S / cm. However, in some embodiments, the conductivity can be as high as 100 S / cm or even 150 S / cm.
[0161] A method of manufacturing a conductive material to be used in a conductive arrangement structure according to the present disclosure may include the steps of 3D printing, 2D printing, screen printing, stencil printing, doctor blade coating, melt processing, molding, slot die coating, inkjet printing, laser printing, solution processing, vacuum filtration, solvent casting and / or papermaking technology.
[0162] In some embodiments, the method further comprises the additional step(s) of adding a crosslinking agent before, during, and / or after applying the composition.
[0163] Applications of DALC bio-ink-based materials
[0164] Conductive materials can be used in sensors. Such sensors can be, for example, capacitive sensors that can be used in many ways. For example, conductive materials can be integrated into materials so that when a characteristic of the material changes, a change in capacitance is detected. This can be, for example, the moisture content of the material, the size / dimensions of the material, and / or the deformation of the material. In other embodiments, the change in capacitance can be detected by an external object, such as a hand or finger touching the sensor and thereby generating a change in capacitance.
[0165] Some embodiments are directed to using conductive materials in electrodes.
[0166] Conductive materials can be used in automotive devices.
[0167] Example
[0168] Example 1. Preparation and evaluation of DALC-based conductive ink
[0169] Materials and methods
[0170] Material
[0171] PEDOT:PSS from Heraeus (Clevios™ PH 1000, 1.3 wt %). Glycerol, sodium periodate, sodium borohydride, polyvinyl alcohol (PVA) and sulfuric acid were all purchased from Sigma Aldrich. All chemicals were used without any further purification.
[0172] Then according to the method reported previously (Larsson, P. A. and L. Towards natural-fiber-based thermoplastic films produced by conventional papermaking. Green Chem. 18, 3324–3333 (2016)). Briefly, pulped bleached softwood kraft fibers (fines removed, fiber concentration 15 g / L) were oxidized to dialdehyde cellulose using sodium periodate (1.35 g / g fiber). The reaction was carried out in the dark and at room temperature for 37 hours, and the pulp was thoroughly washed after the reaction was completed. To determine the aldehyde content, the hydroxylamine titration method was used. The dialdehyde fibers were reduced to diethanol cellulose fibers by adding sodium borohydride (0.4 g / g fiber) and reacted in 0.01 M phosphate buffer for 3 hours. Subsequently, the fibers were thoroughly washed and stored at 4°C until further use. In order to prepare diethanol-modified cellulose nanofibrils, the diethanol-modified cellulose fibers were microfluidized.
[0173] Preparation of DALC-based ink without plasticizer
[0174] To prepare DALC-based conductive inks, diethanol-modified cellulose fibers (modification or substitution degree 10%-50%) or diethanol-modified cellulose nanofibrils (modification degree 10%-50%) were mixed with PEDOT:PSS in different dry weight ratios, wherein the diethanol-modified cellulose (fibers or nanofibrils) consisted of at least 30 wt%, preferably between 30 wt% and 95 wt%, and PEDOT:PSS consisted of at least 5 wt%, preferably between 5 wt% and 70 wt% of the total composition of the ink. All inks also contained a plasticizer consisting of between 1 vol% and 10 vol% of the total composition (corresponding to between approximately 10 wt% and 80 wt% of the total composition). 1 vol%, 5 vol% and 10 vol% of glycerol were used in the preparation of the inks. The inks were placed in a fume hood to evaporate the water to achieve the desired solid content.
[0175] Rheological measurements
[0176] The rheological properties of the inks were measured using a DHR-2 rheometer (TA Instruments, New Cast1e, DE, USA) equipped with a 25 mm parallel plate geometry (1 mm gap distance). All measurements were performed at 25 °C. Each sample was equilibrated for 10 minutes before analysis. The values reported are the average of three replicates. To characterize the linear viscoelastic and flow properties of the inks, the inks with different PEDOT:PSS weight % (e.g. Figure 2 d), and at different solid contents (as shown in Figure 2 a and Figure 2c), at 0.01s -1 With 500s -1 To evaluate the storage modulus (black line) and loss modulus (white line), time sweep measurements were performed and the results are shown in Figure 5b middle.
[0177] SEM and EDS measurements
[0178] A Hitachi S-4800 field emission scanning electron microscope equipped with an energy dispersive X-ray spectroscopy (EDS) detector was used to investigate the morphology and elemental maps. Figure 7 Images (A) and (B).
[0179] Wide-angle X-ray scattering (WAXS)
[0180] A known technique for determining the crystallinity of polymers such as PEDOT is wide angle X-ray scattering (WAXS). Wide angle X-ray scattering measurements were performed using an Anton Paar SAXSpoint 2.0 system (Anton Paar, Graz, Austria) equipped with a micro source X-ray source (Cu Kα radiation with a wavelength of 0.15418 nm) and a Dectris 2D CMOS Eiger R 1M detector. The distance between the sample and the detector was 111 mm. The samples were mounted on a solid sampler (Anton Paar, Graz, Austria), mounted on a VarioStage (Anton Paar, Graz, Austria). The samples were placed under vacuum. For each sample, three frames of 20 minutes duration each were read from the detector. The data obtained using this setup are presented in Figure 8a and Figure 8b Shown in.
[0181] Contact angle measurement
[0182] A contact angle meter (Theta lite, Biolin Scientific) was used to determine the contact angle on the samples, e.g. Fig. 9 The images are shown in (A) and (B).
[0183] result
[0184] Preparation of DALC-based inks.
[0185] As can be understood herein, it has been shown that DALC-modified cellulose can be used as a bio-based alternative to typical polymers in printable conductive inks. Although the reasons are not fully understood, some similarities can be found with, for example, PVA. For example, diethanol-modified fibers have a large number of available polar hydroxyl groups on their surfaces. It was previously known that PVA forms interpenetrating networks with PEDOT:PSS, resulting in strong, stretchable and flexible hydrogels that can be used, for example, in energy storage devices.
[0186] Inks prepared without plasticizers show good processability, but lower conductivity. Moreover, the final material is not wet stable. Thus, plasticizers increase the conductivity of PEDOT:PSS and also help to impart wet stability to the DALC / PEDOT:PSS composite (the reasons for which are not fully understood).
[0187] Figure 5a , Figure 5b , Figure 5c and Figure 5d Rheological analysis of DALC / PEDOT:PSS inks at different PEDOT:PSS wt% (20 wt%, 40 wt% and 70 wt%) is shown, as well as rheological analysis of inks (PEDOT:PSS=40 wt%) at different solid contents (3-10 wt%). Inks with 6%-10% solid content show significant shear thinning and shear yielding behavior, which is a requirement for inks typically required for printing. Inks with lower solid contents (1-5 wt%) are generally required for printing techniques such as blade coating, stencil printing, screen printing, slot die coating or solution processing. Inks with 6-8 wt% solid content are used for 3D printing in subsequent examples.
[0188] The ink shows gel-like behavior at solid content above 3 wt%. Atomic force microscopy (AFM) images of dried samples show that PEDOT:PSS particles are organized on the DALC surface in a pearl necklace-like morphology, as seen in Figure 3. Thus, it can form an entangled network of PEDOT:PSS-covered fibers, providing the gel-like characteristics.
[0189] Interaction between DALC fibers and PEDOT:PSS
[0190] In order to evaluate the distribution of PEDOT:PSS in the DALC / PEDOT:PSS composites, scanning electron microscopy (SEM) images and sulfur mapping images of the 3D printed samples were collected. Figure 7 a and Figure 7As shown in b, they show a surface covered with PEDOT:PSS particles and a layered cross-section, where individual fibers cannot be identified as DALC fibers have film-forming properties. Therefore, due to the excellent film-forming properties of DALC fibers, good conductivity can be achieved due to the uniform adsorption of PEDOT:PSS particles on both the outer and inner surfaces of the fibers.
[0191] An important factor for good conductivity is the removal of free PSS from PEDOT:PSS and thus better packing of PEDOT crystallites. Figure 8a and Figure 8b As can be seen in the figure, WAXS shows a strong PSS peak, which is different from the pure PEDOT:PSS. Offset to 3D printed film (d-spacing 0.51 nm to 0.44 nm), showing a decrease in the stacking distance between PSS crystallites. However, the PEDOT 010 and PEDOT 100 peaks responsible for the π-π stacking of PEDOT crystallites are missing ( Figure 5a On the other hand, after washing the 3D printed film in water, these PEDOT peaks appeared, along with a significantly reduced PSS peak intensity ( Figure 8b ). In addition, the PEDOT 010 peak, typically assigned to the edge orientation of PEDOT crystallites, is lost from the pure PEDOT:PSS The q-value of the 3D-printed sample is shifted to , resulting in a reduced stacking distance (from 0.36 nm to 0.34 nm). However, only a very weak PEDOT 100 peak appears in the 3D printed film, indicating a front-side orientation of the PEDOT crystallites. Therefore, based on WAXS, it can be suggested that DALC fibers not only act as a template for PEDOT:PSS particles, but they also induce the PSS phase separation required for the increased conductivity in PEDOT:PSS (Ouyang et al., 2015). In addition, the close packing of PEDOT crystallites in edge-on orientation is advantageous, which has been shown to be responsible for the high conductivity of PEDOT:PSS. Analysis of morphology and X-ray scattering shows that DALC fibers can induce crystallization in PEDOT:PSS similar to ethylene glycol or other secondary dopants.
[0192] Contact angle measurements of printed DALC / PEDOT:PSS films, such as Fig. 9 a and Fig. 9As shown in b, it is shown that after washing these films, the contact angle increases from 18 degrees for the films used for printing and drying to 121 degrees. This indicates that the surface changes from hydrophilic to hydrophobic due to the enrichment of PEDOT. However, in the pure PEDOT:PSS / glycerol film, the contact angle changes from 14.5 degrees to 38 degrees, which is indeed not that significant. This means that the surface is enriched with more PEDOT domains (because PEDOT is more hydrophobic) and PSS is removed after washing. This effect is more pronounced in the DALC / PEDOT:PSS / glycerol sample than the pure PEDOT:PSS / glycerol sample. Therefore, diethanolcellulose is important for inducing a larger phase separation of PEDOT:PSS.
[0193] In other words, a conductive ink based on diethanol-modified cellulose fibers and PEDOT:PSS was produced that exhibited wet stability. The DALC fibers acted as a template for the PEDOT:PSS particles and facilitated the phase separation of PSS and PEDOT, which resulted in high conductivity in the printed ink even at low PEDOT:PSS content. The use of modified cellulose fibers also eliminated the need for cellulose nanofibrils, which have higher embedding energy and are typically used in bio-based electronic devices.
[0194] Example 2. Processing and electrical characterization of inks
[0195] like Fig.10 a to Fig.10 As shown in d, a direct ink writing 3D bioprinter was used to print different 2D and 3D patterns. Although a 3D bioprinter was used, these inks can also be printed using other printing techniques. These can also be processed using melt extrusion, solution processing techniques, and papermaking techniques.
[0196] Materials and methods
[0197] Inkredible 3D bioprinter The ink was transferred to a syringe, centrifuged for 30 seconds to remove any bubbles introduced during mixing, and dispensed using a high-precision conical nozzle (20G, 25G, and 27G, ) was printed. For each ink composition, the print head speed and printing pressure were adjusted manually. The printed samples were dried in an oven at 60° C. overnight.
[0198] Electrical and electrochemical measurements
[0199] A two-probe conductivity test was performed using a Keithley 2410 source meter. The sample was cut into a rectangle with dimensions of 2 cm x 0.5 cm x (thickness), and the voltage was recorded at a constant current. The resistance was calculated from the slope of the IV curve. The conductivity was calculated using the following formula:
[0200] ρ=(R×w×t) / L
[0201] σ=1 / ρ
[0202] Where ρ is the resistivity, R is the resistance of the sample, w is the width, t is the thickness, L is the distance between the two electrodes, and σ is the conductivity.
[0203] Cyclic voltammetry and galvanostatic charge / discharge measurements were performed using a BioLogic VSP potentiostat with a three-electrode setup. The setup consisted of: Ag / AgCl ( 3M NaCl) reference electrode, platinum counter electrode and 3D printed sample mounted on platinum wire as working electrode; immersed in 1M sulfuric acid as electrolyte. The open circuit potential was recorded before starting each measurement. The specific capacitance of the material was calculated from the discharge cycle as follows:
[0204] C=(I t) / (mΔV)
[0205] Where, I is the discharge current, t is the discharge time, ΔV is the voltage window and m is the mass of PEDOT in the sample.
[0206] The mass of PEDOT in the measured sample was calculated as follows:
[0207] A rectangular piece (20 mm x 5 mm) of the 3D printed DALC / PEDOT:PSS sample was weighed (M0) and then immersed in 1M H2SO4 overnight and then washed thoroughly with milli-q water. The sample was left to dry under ambient conditions and the mass of the dried sample was measured again (Mf). Due to the loss of glycerol from the sample and some PSS present in the sample (the residual electrolyte after sample immersion was transparent), the final weight contained only cellulose fibers and PEDOT:PSS.
[0208] The mass of cellulose and PEDOT:PSS in the printed sample = Mf
[0209] The mass of PEDOT:PSS in the sample calculated based on the initial ratio of the ink (DALC / PEDOT:PSS) = 0.4*Mf
[0210] The mass of PEDOT in the sample = 1 / 3.5*(0.4*Mf), since the original ratio of PEDOT:PSS (as purchased) is 1:2.5 (neglecting the loss of PSS)
[0211] result
[0212] The 3D printed gel has a conductivity of 30 ± 3 S / cm. Fig.11As shown in , the conductivity increases with increasing PEDOT:PSS content to reach a plateau at a PEDOT:PSS content of 40 wt%. This indicates a saturation threshold in the 3D-printed samples, with a conductivity of about 10 S / cm even at 20 wt% PEDOT:PSS, which is good enough for bioelectronic applications. To the best of our knowledge, this is the first demonstration of such good conductivity values obtained for 3D-printed, cellulose fiber-based PEDOT:PSS inks, where the conductive material represents only 20% of the total mass. Moreover, the printed materials are stable in water and physiological solutions for at least 75 days without a significant loss of conductivity, as shown in Figure 2. Fig.12 The rapid conductivity drop in PBS compared to water can be attributed to the dedoping of PEDOT:PSS in the saline solution. The 3D printed patterns are bendable and elastic with 99% conductivity retention, demonstrated here by an LED light that still glows after stretching the printed serpentine pattern ( Fig.13 a and Fig.13 b).
[0213] Electrochemical performance
[0214] To demonstrate the potential of the developed 3D printable conductive ink for energy storage applications, a three-electrode setup was used to analyze the electrochemical performance ( Fig.14 ). Cyclic voltammetry (CV) of materials containing 40 wt % PEDOT:PSS showed ideal supercapacitive behavior, maintaining a quasi-rectangular shape even at a high scan rate of 100 mV / s ( Fig.15 ), i.e., a typical response from an electric double layer capacitor. The constant current charge-discharge (GCD) curve is triangular in shape without a significant potential drop ( Fig.16 ), showing effective charge storage capability due to the high conductivity of the printed working electrode. The gravimetric discharge capacitance is as high as 197 F / g (normalized by PEDOT mass) and the areal capacitance is 170 mF / cm2, even at 10 A / g ( Fig.17 ). The capacitance normalized relative to the mass of the entire electrode is listed in Table 1. As can be seen, the 3D printed samples are close to the theoretical specific capacitance of 210 F / g for PEDOT (Snook et al., 2011), despite the fact that only 40% of the 3D printable ink is PEDOT:PSS. When the PEDOT:PSS content is increased from 20 wt% to 40 wt%, the specific capacitance at a current density of 1 A / g increases from 26 F / g to 211 F / g, but then decreases to 158 F / g (Table 2) if the PEDOT:PSS content is further increased to 70 wt%, i.e. following the same trend as the conductivity values. Again, it is shown that a good conductive network is formed even at low PEDOT:PSS content.
[0215] Electrochemical impedance spectroscopy (EIS) was used to study the ion transport and charge transfer kinetics in the frequency range of 10 MHz to 1 MHz. Before initiating any charge / discharge cycles, the Nyquist plot ( Fig.18 ) shows that in the high frequency range (0.7Ω×cm 2 ) on the real impedance axis, indicating that the printed electrode has a very low intrinsic resistance. The semicircle at the high to medium frequency range indicates the charge transfer resistance. The semicircle disappears after 10,000 charge-discharge cycles, indicating that the charge transfer at the electrode / electrolyte interface is improved during the cycle. This good charge transfer is also the reason why the increased (from 230 to 280 F / g) capacitance is observed after 10,000 cycles ( Fig.19 ).
[0216] Table 1. Specific capacitance and current density values calculated by considering different active material components
[0217] Active mass components Specific capacitance (F / g) Capacitance density (A / g) PEDOT 211 1 PEDOT:PSS 61 0.3 PEDOT:PSS+DALC+glycerol 30 0.1
[0218] Table 2. Specific capacitance values of 3D printed samples with different PEDOT:PSS contents at 1 A / g
[0219] PEDOT:PSS content (by weight) Specific capacitance (A / g) 15 20 26 40 211 70 158
[0220] in conclusion
[0221] The 3D printed samples showed electrochemical performance comparable to state-of-the-art bio-based PEDOT:PSS supercapacitors that used secondary doping such as acid treatment for doping PEDOT:PSS or mixtures of PEDOT:PSS and other redox-active molecules.
[0222] Nyquist curve Fig.18 )The vertical tail in the low-frequency range indicates that the diffusion resistance of the electrode is very low, benefiting from the gel-like electrode structure.
[0223] Example 3. Wearable bioelectronic devices
[0224] Materials and methods
[0225] For electrical and electrochemical measurements, refer to Materials and Methods in Example 2.
[0226] EC-12 test and ECG and EMG measurements
[0227] EC-12 testing was performed at Beneli AB, Sweden, using the SEAM ECG electrode testing platform (QC Integrated, Ontario, Canada) in a gel-gel configuration.
[0228] In order to perform ECG recording, a reference electrode is placed on the abdomen of the person, and then an electrode (gel or printed PEDOT) is placed on each index finger of the person. In order to record the activity generated by the opening and closing of the hand, the reference electrode is placed on the elbow and two printed PEDOT electrodes are placed on the opposite side of the forearm. The same configuration is used and a third electrode is added between the other two to record the signal generated by the hand trace. The RHD2132 amplifier (INTAN Technologies, the United States) is used to record electrical signals on a customized PCB board. The output of the amplifier is connected to an integrated module containing a Spartan-6FPGA (model XEM6010-LX45, Opal Kelly Inc., the United States), and the amplifier is collected from the integrated module by a laptop computer via a USB connection using RHX data acquisition software (Intan Technologies, the United States). In each case, different frequency ranges are used to record signals at a rate of 20kS / s: 1Hz to 100Hz for ECG and 0.1kHz to 1kHz for EMG. The acquired digital signal is processed offline by means of Python programming.
[0229] The power line interference on the signal is removed by applying a second-order 11R digital filter with a cut-off frequency of 50Hz, 100Hz, 150Hz, 200Hz, 300Hz and 400Hz.Fourth-order high-pass and low-pass Butterworth filters are applied at 1kHz and 1Hz respectively to limit the signal to the desired frequency band.The P-QRS-T complex on the ECG signal is detected as a 1s window around the peak, wherein the height is greater than 5 times of the standard deviation of the signal.For hand-sign EMG monitoring, the signal from all three electrodes is first merged to detect the window of the event.The merged signal is squared, smoothed and normalized using the running average of the window with 1000 samples.The 1-sample differential is calculated on the smooth, normalized signal.A threshold of 0.07 is used on the differential to distinguish the event window with EMG activity from the background.On each event window, the power of the signal of each electrode is calculated and standardized by the power of the signal added.
[0230] result
[0231] Due to the stretchability, flexibility and good electrochemical behavior of 3D printed electrodes, it is possible to fabricate supercapacitor devices by twisting two extruded filaments coated with gel electrolyte ( Fig. 20 The dual-electrode device showed a discharge capacitance of 123 F / g and good cycling capability at 3 A / g ( Fig.21 ), demonstrating the potential of the extruded fibers to be woven into textiles for use in wearable energy storage devices.
[0232] In addition, to evaluate the potential of the 3D printed electrodes in electrocardiogram (ECG) monitoring, a standard test was performed (ANSI: AAMI EC12: 2000) for disposable ECG electrodes in an electrode-electrode configuration. The different parameters measured for three different PEDOT:PSS contents are summarized in Table 3a and Table 3b. In addition to default parameters such as AC impedance, DC offset voltage, and noise, the defibrillation discharge was measured, which determines the ability of the electrode to measure ECG after a defibrillation event.
[0233] As can be seen from Table 3, even with as little as 20 wt% PEDOT:PSS, the AC impedance, noise level, and defibrillation discharge have better values than the standard recommendations. To further test and prove the suitability of the material in an ECG monitoring device, the 3D printed electrodes were tested to record ECG signals. A standard 3-lead ECG shows a good ECG signal with clear P-QRS peaks ( Fig. 22 a and Fig. 22 b).
[0234] Table 3a: EC-12 test results for 3D printed electrodes
[0235]
[0236] Table 3b: EC-12 test results of 3D printed electrodes
[0237]
[0238]
[0239] Tsukada et al., 2019 refers in this article to Tsukada, YT et al. Validation of wearable textile electrodes for ECG monitoring. Heart Vessels 34, 1203-1211 (2019).
[0240] Tsukada et al., 2012 herein refers to Tsukada, S., Nakashima, H. & Toimitus, K. Conductive Polymer Combined Silk Fiber Bundle for Bioeletrical Signal Recording. PLOS ONE 7, e33689 (2012).
[0241] in conclusion
[0242] Conductive polymer inks show good electrochemical performance in energy storage as well as body potential monitoring devices. This work paves the way for making greener bioelectronics by using bio-based high-performance conductive inks and enables a step forward in the direction of green devices. Thus, the need for cellulose nanofibrils is reduced, the low weight fraction of the conductive polymer in the 3D ink along with good processability and excellent performance provide scalable and affordable manufacturing of fiber-based wearable electronics.
[0243] Example 4. Printed Microelectrode Array (MEA) Device
[0244] The inks developed herein can be used to measure and monitor electrical potentials from different types of cells, such as cardiomyocytes or nerve cells. They can be cheaper than commercially available gold-based MEAs and do not require patterning techniques for clean-room manufacturing of such devices. Therefore, the cost and time of the manufacturing process for MEAs are saved.
[0245] It will be apparent to those skilled in the art that various modifications and variations may be made in the disclosed devices and systems without departing from the scope of the present disclosure. Other aspects of the present disclosure will be apparent to those skilled in the art by consideration of the specification and practice of the features disclosed herein. The specification and examples are intended to be considered exemplary only. Many additional variations and modifications are possible and are understood to fall within the framework of the present disclosure.
Claims
1. Wearable absorbent articles, including: at least one material layer; as well as a conductor arrangement at least partially deposited on said material layer, optionally printed onto said material layer, The conductor arrangement structure is formed from a composition comprising diethanol cellulose and a conductive material.
2. The wearable absorbent article according to claim 1, wherein The conductor arrangement comprises a sensing device or a part of a sensing device, Or wherein the wearable absorbent article comprises a sensing device or a part of a sensing device in electrical contact with the conductor arrangement.
3. A wearable absorbent article according to claim 2, wherein the sensing device comprises two elements and is configured to measure the resistance between the two elements, or the sensing device is an impedance-based sensor.
4. A wearable absorbent article according to any one of the preceding claims, comprising: a fluid absorbing region for absorbing fluid; as well as an electronic device or a mounting location for mounting an electronic device, The conductor arrangement electrically connects the electronic device or a mounting location for mounting the electronic device to at least one sensing location for detecting moisture in the fluid absorption area.
5. The wearable absorbent article according to claim 4, wherein the fluid-absorbing region comprises an absorbent core, and At least a portion of the conductor arrangement is arranged so as to be electrically insulated from the absorbent core.
6. A wearable absorbent article according to claim 4 or 5, wherein the electronic device comprises a wetness detection unit, the wetness detection unit being removably attached to or embedded within the remainder of the wearable absorbent article.
7. A wearable absorbent article according to any one of the preceding claims, wherein the wearable absorbent article is a diaper, a sanitary napkin, an incontinence garment or a medical dressing, optionally comprising a wound contact layer, an absorbent core and a backing layer.
8. A wearable absorbent article according to any one of the preceding claims, wherein the conductor arrangement comprises a ground electrode and a capacitor electrode, the ground electrode forming a closed loop around the capacitor electrode.
9. A wearable absorbent article according to any one of the preceding claims, wherein the material layer comprises at least one article selected from the group consisting of flexible materials such as nonwovens, films, tissues and fabrics.
10. A wearable absorbent article according to any one of the preceding claims, wherein the conductor arrangement comprises between 5 and 70 wt% of electroactive material, between 30 and 95 wt% of diethanol cellulose and optionally between 10 and 80 wt% of plasticizer.
11. The wearable absorbent article according to any one of the preceding claims, wherein the conductive material comprises a conductive polymer, optionally comprising poly-3,4-ethylenedioxythiophene and polystyrene sulfonate.
12. A wearable absorbent article according to any one of the preceding claims, wherein the conductor arrangement has a conductivity of at least 0.05 S / cm, optionally at least 0.1 S / cm, or at least 0.5 S / cm, or at least 1 S / cm.
13. The wearable absorbent article according to any one of the preceding claims, wherein the diethanolcellulose comprises fibers having a diameter of at least 1 μm, such as at least 5 μm, such as at least 8 μm, such as at least 12 μm.
14. A method of making a wearable absorbent article comprising the steps of: - providing an absorbent article comprising at least one material layer; as well as - depositing a composition comprising diethanol cellulose and a conductive material on the at least one material layer to form a conductor arrangement structure on the at least one material layer.
15. The method of manufacturing a wearable absorbent article according to claim 14, wherein the composition is deposited on the at least one material layer by any one or more of the following techniques: 3D printing, 2D printing, screen printing, stencil printing, doctor blading, melt processing, slot die coating, inkjet printing, laser printing, solution processing, vacuum filtration, solvent casting, and papermaking technology, and in, Optionally, the composition is at least partially dried and / or cured before, during and / or after applying the composition.
16. A method of manufacturing a wearable absorbent article according to claim 14 or 15, wherein the method further comprises one or more additional steps of adding a cross-linking agent before, during and / or after applying the composition.
17. A method of manufacturing a wearable absorbent article according to any one of claims 14 to 16, wherein the cross-linking agent is added before, during and / or after applying the composition.
18. An absorbent article manufactured according to the method of any one of claims 14 to 17.
